PERLINDUNGAN KONSUMEN : REGULASI BISNIS LABEL HALAL - SLAMET MUJIONO (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
Consumer protection against halal food seems to get less attention. Based on the research results YLKI complaints relating to halal food very little. But at least the complaint against kosher food does not mean that Indonesian Muslims do not care about the food and drinks are not permitted to circulate freely without Halal certification. During this Indonesian Muslims believe in the MUI for halal products. In business regulation, consumer protection Muslims for halal products not only in the form of halal labeling contained in food safety laws. However, we must have integrity and other economic laws, so there is no guarantee the implementation of halal labeling. It is strongly associated with things that are businesses, such as trade agreements, distribution, advertising, packaging, negligence and abuse of halal labeling. Muslim consumer protection is likely to be equated with consumer protection in general in Indonesia to enact legislation contains consumer protections contained in Economic Law Indonesia. Due to the halal labeling is closely related to the implementation of Islamic law, the Consumer Protection Law in Indonesia at least absorbing elements, values and norms contained in Islamic law especially were very closely related to consumer protection, labeling halal and business regulasasi Products- halal products in Islamic economics. Based on the description above key issues discussed was how the consumer protection Muslims for halal products in the Islamic Business Ethics Regulation.